L-fucose and fucoidan alleviate high-salt diet-promoted acute inflammation - Li, Wenhua; Wu, Pengfei; Jin, Tianrong; Jia, Jialin; Chen, Bo; Liu, Tingting; Liu, Yu; Mei, Jie; Luo, Bangwei; Zhang, Zhiren (Frontiers in Immunology, 2024)
Excessive salt intake is a widespread health issue observed in almost every country around the world. A high salt diet (HSD) has a strong correlation with numerous diseases, including hypertension, chronic kidney disease, and autoimmune disorders. However, the mechanisms underlying HSD-promotion of inflammation and exacerbation of these diseases are not fully understood. In this study, we observed that HSD consumption reduced the abundance of the gut microbial metabolite L-fucose, leading to a more substantial inflammatory response in mice. A HSD led to increased peritonitis incidence in mice, as evidenced by the increased accumulation of inflammatory cells and elevated levels of inflammatory cytokines, such as tumour necrosis factor alpha (TNF-α), interleukin 6 (IL-6), and monocyte chemotactic protein-1 (MCP-1, also known as C-C motif chemokine ligand 2 or CCL2), in peritoneal lavage fluid. Following the administration of broad-spectrum antibiotics, HSD-induced inflammation was abolished, indicating that the proinflammatory effects of HSD were not due to the direct effect of sodium, but rather to HSD-induced alterations in the composition of the gut microbiota. By using untargeted metabolomics techniques, we determined that the levels of the gut microbial metabolite L-fucose were reduced by a HSD. Moreover, the administration of L-fucose or fucoidan, a compound derived from brown that is rich in L-fucose, normalized the level of inflammation in mice following HSD induction. In addition, both L-fucose and fucoidan inhibited LPS-induced macrophage activation in vitro. In summary, our research showed that reduced L-fucose levels in the gut contributed to HSD-exacerbated acute inflammation in mice; these results indicate that L-fucose and fucoidan could interfere with HSD-promotion of the inflammatory response.